The impact of equal parenting time laws on family outcomes and risky behavior by teenagers: evidence from Spain - Nollenberger, Natalia; Fernández Kranz, Daniel (IE University, 2021)
Due to legal reforms, equal parenting time (EPT) laws in Spain now apply to approximately 40% of all divorces, with likely implications for family outcomes and teenagers’ risky behavior. Consistent with theories of bargaining power within marriage, we find that EPT laws decrease contentious and wife-initiated divorces and increase the employment of mothers relative to fathers. An analysis of drug use and family relationships, among 165,000 teenagers, further shows that EPT laws significantly decrease risky behavior by teenagers, especially boys, who claim to have better relationships with their father, although more unclear norms for behavior. These results have some international implications, such as for the United States, where more than half of the states are considering whether to adopt EPT laws.
Keywords: Equal parenting time; Shared parenting; Joint physical custody; Divorce; Female labor force participation; Adolescent behavior; 63 Sociología; ODS 5 - Igualdad de género